The modern anti-hadith movements in Pakistan: A study on perception of Muslim youth in Punjab-Pakistan / Anam Bashir - Anam , Bashir (2023)
Anti-Hadith Movement also known as the Quranists movement in Pakistan led by some modern Muslim scholars particularly Ghulam Ahmed Pervez and Javed Ahmed Ghamidi. This movement proposed confusing ideologies and propagating misconceptions about the status of Hadith in Islam. This movement reflects Muslim youngsters, especially those who believe in independent thinking and modernization of Islam. Therefore, this study examines the understanding of the public towards the Anti-Hadith Movement in Pakistan particularly the perception of Muslim youth towards their deviations, objectives, and strategies. The quantitative research of survey has been applied in this study of which 197 students living in Punjab Pakistan are chosen as sample of respondents. The study found that the understanding of Muslim youth in Punjab regarding the ideologies of anti-hadith movements at a moderately low level. Their perceptions and attitudes towards the anti-hadith movements and their awareness on basic sources of Islam at a moderately high level. The study revealed that the main factor of shaping this perception is the absence of Islamic education among Muslim youth of Pakistan and the excessive impact of social media as a platform of propagation of anti-Hadith ideas. As a result, a significant number of Pakistani youths in Punjab are unable to comprehend the fundamental teachings of Islam. Therefore, they are in danger of being influenced by anti-Hadith movements.